Employers' emphasis on technical skills and soft skills in job advertisements - Ooi, Kien Bee; Ting, Su Hie (Malaysian English Language Teaching Association, 2015)
This study examined the emphasis placed on technical and soft skills in job advertisements for various industries. A total of 105 job advertisements in newspapers and jobstreet.com were analysed. The results show that almost all the job advertisements mention relevant degrees for the job and a portion of them require some working experience, indicating that employers expect job applicants to have the necessary technical skills for the position. Among the soft skills, communication skill and teamwork are the two most sought after skills but the type of soft skills required varies with the position and the industry. However, contrary to the focus on teamwork and leadership skills in college and university soft skill training, the analysis indicates that the employers value ability to work independently and to produce quality work under pressure and tight deadlines more. The results of this study provide data-driven evidence for lecturers teaching business communication and English for professional communication on the important aspects to focus on when teaching students to write job application letters and resumes.